Imagined differences: hatred and the construction of identity - Schlee, Günther (Market, culture and society, 2002)
Introduction : Approaches to 'identity' and 'hatred' : some Somali and other perspectives / G(c)ơnther Schlee -- Switching identity discourses : primordial emotions and the social construction of we-groups / Georg Elwert -- Temperamental neighbours : Uighur-Han relations in Xinjiang, northwest China / Ildik(c)đ Bell(c)♭r-Hann -- Murder in the cathedral : disrupted time, broken space : violence in the regional history of an Indonesian church / Philip Quarles van Ufford -- Lances greased with pork fat : imagining difference in Bali / Mark Hobart -- Religion, modernity, tradition and the construction of difference inside an Egyptian village / Petra Weyland -- The multidimensionality of Oromo identity / Georg Haneke -- Writing the nation : the pre-war Indonesian nationalist novel / Thomas Rieger -- Politics and Berber identities in Morocco / Bernhard Venema -- Exclusivist rhetorics : the constitution of political identities in present-day Algeria / Birgit Mara Kaiser -- Combat modes, mimesis and the cultivation of hatred : revenge/counterrevenge killings in Sri Lanka / Purnaka L. de Silva -- Targeting the victims of violence : the role of folk history and voluntary associations in the construction of hatred in Northern Ireland / Mary Catherine Kenney -- Regularity in chaos : the politics of difference in the recent history of Somalia / G(c)ơnther Schlee